External patient visits and healthcare service delivery at terara public health center: A management perspective analysis - Nurhayati, Nurhayati; Sastrawan, Sastrawan; Sismulyanto, Sismulyanto; Saimi, Saimi; Menap, Menap (Institute of Computer Science (IOCS), 2024)
The increasing visits of patients from outside the area to Terara Public Health Center constitute a phenomenon of growing significance within the context of healthcare provision in the region. This necessitates an understanding of the impact of these external patient visits on healthcare service delivery at Terara Public Health Center, encompassing aspects such as resource availability, operational efficiency, and service management. Therefore, this research aims to analyze the management perspective regarding the influence of external patient visits on healthcare provision at Terara Public Health Center. This research employs a descriptive method with a qualitative approach. Data collection takes the form of words or images, thus not focusing on numerical data. The intention of this study is to provide an overview, elucidate, and interpret the current situation regarding the impact of external visits on healthcare services at Terara Public Health Center from a service management perspective. This research was conducted at Terara Public Health Center. The findings indicate that the high influx of patients from outside the area to Terara Public Health Center has a significant impact on service management, including increased patient queues, maintenance costs of medical equipment, availability of medications, and the need for more adequate facilities and infrastructure. Management at Terara Public Health Center has taken steps to address these impacts, such as increasing the procurement of medications and enhancing facilities and infrastructure.